Pregnancy snapshot: a retrospective, observational case–control study to evaluate the potential effects of maternal diabetes treatment during pregnancy on macrosomia. (2nd July 2016) - Shannon, Michael H.; Wintfeld, Neil; Liang, Michael; Jovanovic, Lois
Abstract: Objective : Pregnancy in women with diabetes is associated with increased incidence of macrosomia (high birth weight) versus women without diabetes. Macrosomia increases the risk of complications during delivery and neonatally. The potential effect on macrosomia incidence certain diabetes treatments may have is not fully established. This study aims to identify whether specific components of the prenatal care of mothers with diabetes are associated with increased macrosomia risk in a real-world U.S. setting.Research design and methods : Retrospective, observational case-controlled study of mothers either without diabetes, or with type 1 (T1D), type 2 (T2D), or gestational diabetes mellitus (G.D.M.), using data from a U.S. insurance claims database. Treatment selection was at physician discretion.Main outcome measure : Incidence of macrosomia.Results : For mothers with T2D, use of neutral protamine Hagedorn (N.P.H.) insulin and glyburide increased during pregnancy, from 3.4% to 33.3%, and 3.7% to 16.5%, respectively. The most common G.D.M. treatments during pregnancy were glyburide (15.5%), N.P.H. (12.9%), basal–bolus therapy (10.0%), and metformin (8.1%). Endocrinologist care during pregnancy was associated with insulin use – but not glyburide use – for mothers with G.D.M., and with insulin use for mothers with T1D and T2D (compared with mothers not visiting an endocrinologist). Glyburide was associated with higher odds for macrosomia: G.D.M. (odds ratio [O.R.] 1.53, 95% confidence interval [C.I.] 1.38–1.69, p < 0.0001); T2D (O.R. 1.93, 95% C.I. 1.51–2.47, p < 0.0001). Endocrinologist care was associated with lower odds for macrosomia overall (O.R. 0.86, 95% C.I. 0.81–0.92) and for mothers with G.D.M. (O.R. 0.85, 95% C.I. 0.75–0.97, p = 0.0156) when the sub-populations were examined in separate models.Conclusions : Healthcare utilization and endocrinologist care were related to positive birth outcomes, especially with G.D.M. Further research into the safety and efficacy of glyburide in pregnancy is warranted. This study cannot infer causality and may not be representative of current U.S. healthcare practice.